The Phenomenon of Political Power in Ukraine - Bereziuk, Sergiy; Pronko, Lyudmila; Samborska, Oksana (European Journal of Sustainable Development, 2020)
Political power is the integral part of constituent of development and stability of society, that is why her efficiency are one of main tasks of domestic politics. Success of the state depends in the international political arena, first of all, from experience and professionalism of own political management. Studies of scientists from the marked theme full have not fully covered the of problems, it is today necessary to work out the own effective model of politics, that would connect success and experience of international association, Ukrainian history, traditions and customs. Main reason of the crisis phenomena in Ukrainian society see in absence of clear strategy of development and absence of professional competenses of politicians, in relation to state creation. The purpose of the study is to find out the essence of political power and influence on the effectiveness of state-building, substantiation of directions of increasing the effectiveness of political power in Ukraine on the basis of political intelligence. Keywords: state, politics, development, post-soviet countries, reform, president